Strengthening sustainable small-scale aquaculture and fisheries through proper infrastructure and policy - Pratiwi Ayu; Farikhah; Adiputra Yudha; Lee Guenwoo; Adiputri Ratih (The Think20 (T20), 2022)
Small-scale aquaculture and fisheries actors globally are faced by suboptimal value chain problems, weak environmental planning and waste management, and inadequate food safety and nutrition standards. These limitations hampered the smallholders from effectively participating in the responsible and sustainable value chain processes, consequently threatening their livelihood. This policy brief addresses comprehensive and interlinked recommendations in areas where immediate action is needed, namely to increase investment in fishery/aquaculture supply chain upgrading, to support environmentally responsible water management and biodiversity preservation, and to promote fish as a nutritious food source and synergize social protection programmes at local and national levels.